Answer:
Completing the square the equation that would be used to solve 0=-x^2+10x-8 is (x-5)^2=17 (Second option).
Explanation:
0=-x^2+10x-8
Moving the terms with the variable x to the left side of the equation:
0+x^2-10x=-x^2+10x-8+x^2+10x
x^2-10x=-8
Adding both sides of the equation the square of the half of the coefficient of "x" to complete the square on the left side of the equation:
x^2-10x+(10/2)^2=-8+(10/2)^2
x^2-10x+(5)^2=-8+(5)^2
x^2-10x+25=-8+25
x^2-10x+25=17 (1)
Using that (x-a)^2=x^2-2ax+a^2 with
2a=10→2a/2=10/2→a=5
or a^2=25→sqrt(a^2)=sqrt(25)→a=5
x^2-10x+25=(x-5)^2
Then replacing x^2-10x+25 by (x-5)^2 in the equation (1)
(1) (x-5)^2=17